Photophysical and photochemical properties of novel metallophthalocyanines bearing 7-oxy-3-(m-methoxyphenyl) coumarin groups - Tastemel, Aysegul; Karaca, Birsen Yilmaz; Durmuş, Mahmut; Bulut, Mustafa (Elsevier Science Bv, 2015)
Tetra-peripherally and non-peripherally 7-oxy-3-(m-methoxyphenyl)coumarin-substituted zinc(II) (4a and 5a), indium(III)acetate (4b and 5b) and magnesium(II) (4c and 5c) phthalocyanines were synthesized for the first time. These phthalocyanines were characterized by elemental analysis, FT-IR, H-1 NMR, UV-vis spectroscopy and mass spectra. The novel phthalocyanines showed excellent solubility in general organic solvents, such as dichloromethane, chloroform, tetrahydrofuran (THF), N,N-dimethylformamide (DMF) and dimethylsulfoxide (DMSO). The photophysical and photochemical properties of these phthalocyanines were investigated in DMF. The effects of the central metal ions (Zn2+, Mg2+, In+3) and the position (peripheral or non-peripheral) of the substituents on the photophysical and photochemical parameters were reported for comparison. The singlet oxygen quantum yield values of novel phthalocyanines ranged from 0.29 to 0.82 in DMF. In this study, the fluorescence quenching behavior of the studied zinc(II) and magnesium(II) phthalocyanine complexes was also described by the addition of 1,4-benzoquinone. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Coumarin (2H-chromen-2-one, 2H-1-benzopyran-2-one); Fluorescence; Quantum yield; Singlet oxygen; Quenching